Antioxidant and Antibacterial Activities of Four Local Medicinal Plants (Plant Tissue Culture and Biotechnology, 2020)
Potential antioxidant and antibacterial activity of methanolic, chloroformic and n-hexane leaf extracts of four local important medicinal plants like Ocimum americanum, O. basilicum, O. gratissimum and Centella asiatica was investigated. The methanolic leaf extracts of these plant species exhibited the potent DPPH free radical scavenging activity (IC50 value, 2.67 ± 0.01, 14.17 ± 0.11, 60.22 ± 0.01 and 2.39 ± 0.025 μg/ml, respectively). Methanolic leaf extract of C. asiatica showed strongest antioxidant activity. Chloroformic leaf extracts possessed moderate antioxidant activity (IC50 value of 79.44 ± 0.05, 110.56 ± 0.02, 54.95 ± 0.05, 101.0 ± 1.0 μg/ml, respectively) in all samples. The lowest antioxidant activity was recorded from n-hexane leaf extracts of O. americanum, O. gratissimum, C. asiatica and Ocimum basilicum (IC50 value 147.87 ± 0.06, 378.19 ± 2.65, 104.65 ± 0.39, 467.58 ± 0.52 μg/ml, respectively). Methanolic and chloro-formic leaf extracts showed antibacterial activity against both Gram-positive and Gram-negative pathogenic bacteria, namely Bacillus megaterium, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhi. Methanolic leaf extract of O. americanum and chloroformic extract of C. asiatica showed excellent antimicrobial activity.Plant Tissue Cult. & Biotech. 30(2): 179-187, 2020 (December)